PENGEMBANGAN PERMAINAN LEGO KIMIA SEBAGAI MEDIA PEMBELAJARAN SUB MATERI KONFIGURASI ELEKTRON PADA SISWA KELAS X SMA MUHAMMADIYAH 1 PONTIANAK - Della Indika Juniarni; Raudhatul Fadhilah; Rizmahardian Ashari Kurniawan (Jurnal Ilmiah Ar-Razi, 2019)
The students problem in understanding the electron configurations was caused by the ineffective learning media which is used by the teacher didn’t fit the student’s characteristic. Therefore, it is important to develop media of Lego Chemistry games for electron configurations class. The validation of the media is validated in three aspects. They were validity from the results of the game, practicality from the results of the questionnaire, and the effectiveness from the results of the pre and post tests. This study used a Research and Development (R & D) model of Borg and Gall conducted in seven stages. The study showed that media of Lego Chemistry games was suitable for teaching learning process. It can be seen from the results of the material and media aspects by 0,83 and 0,94 which was valid. The results of the practicality of the questionnaires on the small and main tryouts were 92,50% and 90,66% and were considered practical. The results of the effectiveness of the N Gain on the small and main tryouts were 0.74 and 0.92 (high). Therefore, media of Lego Chemistry games was valid and effective. It is suitable to be used as the learning media in Chemistry class.